THE EFFECT OF COGNITIVE BEHAVIOR MODIFICATION ON REDUCING ACADEMIC PROCRASTINATION AMONG STUDENTS AT MADRASAH ALIYAH SEHATI MAROS - Nur Ainun Maghfira; Farida Aryani; Suciani Latif (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the effect of applying Cognitive Behavior Modification (CBM) using the self-instruction technique in reducing academic procrastination behavior among students of Madrasah Aliyah Sehati Maros. The study employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group design. The research subjects consisted of 20 students divided into an experimental group and a control group. Data were collected using an academic procrastination scale developed based on Ferrari’s theory and were supported by observations and interviews conducted during the intervention process. Data analysis techniques included descriptive analysis, normality tests, homogeneity tests, t-tests, and effect size calculations. The results showed that the level of academic procrastination in the experimental group decreased significantly from the high category in the pretest to the low category in the posttest, while the control group remained in the high category. These findings indicate that the application of the Cognitive Behavior Modification approach with the self-instruction technique is effective and significant in reducing academic procrastination behavior among students. This study provides practical implications for guidance and counseling services in madrasahs in developing cognitive-behavioral–based interventions to enhance students’ learning discipline and academic responsibility.